Characterization of the annual regime of surface solar irradiance over Argentine Pampean Region using GL 1.2 satellite-based data - Ceballos, Juan Carlos (2022)
Detailed description of the solar resource (spatial distribution and temporal variations) is highly desirable in the context of climate monitoring, agricultural planning and energy technologies; however, one shortcoming is the low density of solarimetric networks in many extended regions. Satellite-based estimations have become a potential key tool, provided their data show adequate temporal frequency, high resolution and acceptable accuracy. GL1.2 Model currently runs at Brazilian National Institute for Space Research (CPTEC/INPE), based on GOES VIS channel imagery. It was tested for characterizing solar radiation regime over Pampa Region in Argentina, which extends over more than 600,000 km2. Comparison with time series of nine stations of the Pampa network in the period 2011–2018 showed close agreement for daily mean irradiance using 10-days as well as monthly values (mean bias error generally |MBE| < 6 W m-2 standard deviation STD ≈ 10-15 W m-2 and resulting root mean square error RMSE ≈ 10–16 W m−2). Completeness of GL time series and high spatial definition (0.04°) allowed further time and space analysis of solar radiation regime. It confirmed that Pampean region is rather homogeneous with annual mean GL increasing from 185 W m−2 on coastal region up to 220 W m−2 on the western and northern limits. In addition, GL data detects sharper variations in a scale of few kilometers, such as transition between ground and water in oceanic coast or large rivers. Regional interannual variability is low: COV ≈ 3–4%. All stations in Pampa network show a well definite annual cycle, closely followed by GL estimates. Fourier analysis for GL monthly series shows a dominant deterministic one year signal (H8 harmonic), accounting for 93–95% of variance for all stations and throughout the Pampa region, in phase with the end of Southern Hemisphere spring. The H8 amplitude varies from 100 W m−2 along inner continental boundary up to 120 in southwestern and coastal bound. It is concluded that GL 1.2 model data can be used to accurately describe time series of daily mean irradiance, for 10-days and monthly scales and 4 km resolution, providing a "Test Reference Year" (TRY). This is precious in order to describe spatial-temporal patterns of regional solar climate. An otherwise "random signal" of 20 W m−2 is associated to transient meteorological phenomena with durations shorter than 10-days, such as cold fronts or convective activity. Their deterministic and/or statistical structure could be improved by the combined analysis of short-time scales Pampa network and GL data (daily, hourly or even minutely).